Splenectomies: a rewiew of 103 cases - Parma, Dante; Armand Ugon, César; Otazu, Hebert (Cirugía del Uruguay, 1981)
The authors review medica] and surgical indications of splenectomies and contribute with a case material consisting of 103 patients from Surgical Clinics Nł 1 in the Pasteur Hospital of Montevideo.